Luminescent Iridium Complex-Peptide Hybrids (IPHs) for Therapeutics of Cancer: Design and Synthesis of IPHs for Detection of Cancer Cells and Induction of Their Necrosis-Type Cell Death - Abdullah-Al Masum; Yosuke Hisamatsu; Kenta Yokoi; Shin Aoki (Bioinorganic Chemistry and Applications)
Death receptors (DR4 and DR5) offer attractive targets for cancer treatment because cancer cell death can be induced by apoptotic signal upon binding of death ligands such as tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) with death receptors. Cyclometalated iridium(III) complexes such as fac-Ir(tpy)3 (tpy = 2-(4-tolyl)pyridine) possess a C3-symmetric structure like TRAIL and exhibit excellent luminescence properties. Therefore, cyclometalated Ir complexes functionalized with DR-binding peptide motifs would be potent TRAIL mimics to detect cancer cells and induce their cell death. In this study, we report on the design and synthesis of C3-symmetric and luminescent Ir complex-peptide hybrids (IPHs), which possess cyclic peptide that had been reported to bind DR5. The results of 27 MHz quartz-crystal microbalance (QCM) measurements of DR5 with IPHs and costaining experiments of IPHs and anti-DR5 antibody, suggest that IPHs bind with DR5 and undergo internalization into cytoplasm, possibly via endocytosis. It was also found that IPHs induce slow cell death of these cancer cells in a parallel manner to the DR5 expression level. These results indicate that IPHs may offer a promising tool as artificial luminescent mimics of death ligands to develop a new category of anticancer agents that detect and kill cancer cells.